2011
DOI: 10.1590/s1415-43662011001000001
|View full text |Cite
|
Sign up to set email alerts
|

Resposta de cultivares de alface à salinidade da solução nutritiva com rejeito salino em hidroponia

Abstract: R ESU M ONo processo de dessalinização se gera, além da água potável, um rejeito altamente salino e de poder poluente elevado, o qual pode ser utilizado na produção agrícola rentável dependendo da adoção de práticas culturais adequadas e da tolerância das plantas às condições salinas. Nos últimos anos a tendência tem sido a substituição da agricultura convencional por sistemas hidropônicos de cultivos, considerados um dos mais eficientes no uso de água. O objetivo desta pesquisa foi analisar a resposta de duas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
15

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 9 publications
(8 reference statements)
0
8
0
15
Order By: Relevance
“…Other authors have also observed reduction in leaf area of lettuce as a function of the increase in the salinity of the nutrient solution (Dias et al, 2011;Moraes et al, 2014). Studies on other crops have also shown adverse effects of saline stress on leaf area as a function of increase in saline levels; for instance, Dias et al (2010) in muskmelon (Cucumis melo) and Souza et al (2010) in physic nut (Jatropha curcas L.).…”
Section: Resultsmentioning
confidence: 90%
“…Other authors have also observed reduction in leaf area of lettuce as a function of the increase in the salinity of the nutrient solution (Dias et al, 2011;Moraes et al, 2014). Studies on other crops have also shown adverse effects of saline stress on leaf area as a function of increase in saline levels; for instance, Dias et al (2010) in muskmelon (Cucumis melo) and Souza et al (2010) in physic nut (Jatropha curcas L.).…”
Section: Resultsmentioning
confidence: 90%
“…Studies in the literature confirm that the use of brackish water is related to the crop tolerance to salt stress (SOARES et al, 2007;PAULUS et al, 2010;DIAS et al, 2011a;DIAS et al, 2011b;OLIVEIRA et al, 2011), and most of them were performed with lettuce crops (Lactuca sativa L.), which stands out in Brazil as the most produced vegetable in the hydroponic system Nutrient Film Technique (NFT) (PAULUS et al, 2012).…”
Section: Introdutionmentioning
confidence: 99%
“…In Brazil, this vegetable has great economic and social importance, because its production has a relatively low cost, besides a high demand for labor, allowing small properties to cultivate it, thus generating jobs and income (Alves et al, 2011;Dias et al, 2011;Lúcio et al, 2011;Santos et al, 2011;Paulus et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the producers are forced to utilize irrigation as a way to overcome this problem Santos et al, 2011;Sarmento et al, 2014). However, the lower quality of the water available for agricultural use in this region leads to large problems in the economic potential of lettuce cultivation, due to the presence of high contents of salts in the irrigation water (Alves et al, 2011;Dias et al, 2011;Oliveira et al, 2011;Santos et al, 2011;Sarmento et al, 2014).…”
Section: Introductionmentioning
confidence: 99%